Vitamin D and the brain: Genomic and non-genomic actions - Cui, Xiaoying; Gooch, Helen; Petty, Alice; McGrath, John J.; Eyles, Darryl (Molecular and cellular endocrinology, 2017)
1,25(OH)2D3 (vitamin D) is well-recognized as a neurosteroid that modulates multiple brain functions. A growing body of evidence indicates that vitamin D plays a pivotal role in brain development, neurotransmission, neuroprotection and immunomodulation. However, the precise molecular mechanisms by which vitamin D exerts these functions in the brain are still unclear. Vitamin D signalling occurs via the vitamin D receptor (VDR), a zinc-finger protein in the nuclear receptor superfamily. Like other nuclear steroids, vitamin D has both genomic and non-genomic actions. The transcriptional activity of vitamin D occurs via the nuclear VDR. Its faster, non-genomic actions can occur when the VDR is distributed outside the nucleus. The VDR is present in the developing and adult brain where it mediates the effects of vitamin D on brain development and function. The purpose of this review is to summarise the in vitro and in vivo work that has been conducted to characterise the genomic and non-genomic actions of vitamin D in the brain. Additionally we link these processes to functional neurochemical and behavioural outcomes. Elucidation of the precise molecular mechanisms underpinning vitamin D signalling in the brain may prove useful in understanding the role this steroid plays in brain ontogeny and function. •Vitamin D modulates neurogenesis in the developing brain.•Developmental vitamin D deficiency regulates the development of the dopaminergic system.•Vitamin D regulates neurotransmitter release in the adult brain.•Vitamin D exerts its neuroprotection in the aged brain.•Vitamin D evokes calcium influx via its rapid non-genomic actions.